Public supervision on the public procurement market in selected EU member states (selected aspects) - Gola, Jan (Publiczny nadzór nad rynkiem zamówień publicznych w wybranych krajach członkowskich Unii Europejskiej (wybrane aspekty), 2020)
The article relates to the issue of the public supervision held by specialised bodies responsible for the proper functioning of the system of public procurements in individual member states of the European Union. Minimisation of the risk of irregularities in the field of public procurements requires a multi-aspect approach, including the efficient performance of activities performed within the carried out supervision. Juridical solutions relating to the discussed subject matter, applied by the legislators of the individual states, will be presented in the article. Attention is drawn to improper regulations that should be changed by the legislators of the indicated EU member states, which are often unclear and conflict with each other. Moreover, the EU law concerning to public supervision over the public procurement market, which should be applied in all member states, must be addressed. The de lege ferenda conclusions and proposals presented in the article will contribute to the more effective functioning of the public procurement market. The study was prepared within the framework of a research project funded by the National Science Centre – decision DEC-2014/14/E/HS5/00845
Ekonomia XXI Wieku = Economics of the 21st Century, 2020, Nr 23, s. 35-44